Predictors of length of stay after urogynecological surgery at a tertiary referral center. (February 2017) - Gagnon, Louise-Helene; Tang, Selphee; Brennand, Erin
Abstract Introduction and hypothesis The primary objective of this study was to determine significant predictors of length of stay (LOS) beyond the first postoperative day after urogynecological surgery. Methods A single-center retrospective cohort study was conducted in 2015. Our study population included women who underwent inpatient pelvic reconstructive surgery. The primary outcome was LOS beyond the first postoperative day. A logistic regression analysis explored the relationship between 11 selected predictor variables [age, body mass index (BMI), American Society of Anesthesiologists (ASA) score, distance from home to hospital, length of surgery, anesthesia during surgery, route of surgical approach, trial of void recordings, choice of bladder protocol, presence of concomitant sling, surgeon], and LOS. Results Two hundred and sixty-three patients were included in this study. A logistic regression analysis identified route of surgery and trial of void recordings as the two statistically significant predictors of stay beyond the first postoperative day. The odds of LOS after laparoscopic or open surgery compared with vaginal surgery increased more than fivefold [laparoscopic vs. vaginal approach odds ratio (OR) 5.04, 95 % confidence interval (CI) 1.95–13.03; laparotomy vs. vaginal OR 15.56, 95 % CI 1.77–136.77] and more than threefold for a prolonged pass of the bladder protocol compared with an immediate pass (OR 3.25, 95 % CI 1.54–6.87). Conclusion Our study identified route of surgery and trial of void recordings as the two predictors with the greatest impact on LOS beyond the first postoperative day. Our results warrant a larger follow-up study.